AKSESIBILITAS PENYANDANG DIFABEL PADA KOTA TUA AMPENAN - DHARMA S., BAGUS WIDHI (Universitas Mahasaraswati Mataram, 2018)
The equality of the right to enjoy and use facilities is the right of all citizens, even everyone in Indonesia. Likewise in Ampenan Old Town Park area as a public facility must be able to accommodate the needs of its users.This study aims to find out the accessibility facilities that are already available in the Ampenan Old City Park, the condition of the facility can be known by conducting a survey and direct observation to the location. The necessary requirements for park accessibility are carried out with references in the form of literature books and guidance from the government and regulations issued by the government for people with disabilities. The analysis is carried out by comparing the conditions in the Ampenan Old City Park with those in government regulations. By conducting this research, it is known that the facilities that are available are still very minimal, the facilities in the form of yellow directional floor tiles are installed in the middle of the sidewalk used for provide direction information for blind people, the condition of the facility does not meet the requirements as a director. Other facilities are not yet available to become an inclusive park. The results of this study can be used as a reference for the importance of implementing government regulations in the form of Permen PUPR No.14 / PRT / M / 2017 for the provision and construction of public facilities that can be used by people with disabilities. Taman Kota Tua Ampenan is equipped with good accessibility facilities, so that visitors who can use, enjoy and have maximum activities